## (Section 10)

#### Use the graph calculator to create the graphs and tables of y1 = x2 and y2 = (x+1)2.

 Graphs of y1 = x2 and y2 = (x+1)2 Table values of y1 = x2 and y2 = (x+1)2

Remember the base function y1 = x2 passes through (0,0), so y1 is the graph on the right.  What happens to the graph when x is replaced with the quantity x+1?  (The graph moves one unit to the left.)

Study the set of table values associated with each function to see how they are changed by replacing x with x+1.

(To obtain the same y values a value of x one less must be used. For example to obtain the value of 4 in y1 we use x = 2 or -2.  But to obtain a value of 4 in y2 we need to use 1 or -3.  These x values are one less.)

##### Use the graphing calculator to look at graphs and tables of y1=|x| and y2=3|x|.
 Graphs of y1=|x| and y2=3|x| Table values of y1=|x| and y2=3|x|

Remember the base function y1=|x| pass through the origin and the lines have slopes of 1 and -1.  What happens to the graph when the function is multiplied by 3? (The values of the function are multiplied by 3 or they become larger.)

Study the set of table values associated with each function to see how they are changed by multiplying by 3.

(The y values from y1 are multiplied by 3 to get the y values for y2.  This means the y values will be higher for each x value.  So the graph of y=3|x| shows steeper lines.  No shift will take place, just a vertical stretch.)

##### Use the graphing calculator to create graphs and tables of y1=3x and y2=3-x.
 Graphs of y1=3x and y2=3-x Table values of y1=3x and y2=3-x

Remember the base function  y1=3x begins in quadrant II and passes through the (0,1) and continues through quadrant I.  What happens to the graph when the x is replaced by -x.  (The graph is reflected over the y-axis.)

Study the set of table values associated with each function to see how they are changed by the replacement of x with -x.

(Studying the y values you can notice that y2(1)=y1(-1), y2(2)=y1(-2) or in general the table for y1 has been turned upside down to produce the table for y2.  This causes the graph to be reflected over the y-axis.)

##### Use the graphing calculator to create graphs and tables of y1=3x and y2=-3x.
 Graphs of y1=3x and y2=-3x Table values of y1=3x and y2=-3x

Remember the base function y1=3x  begins in quadrant III and passes through the point (0,1) and continues through quadrant I.  What happens to the graph when the y=f(x) when it is changed to y=-f(x)?  (The graph is reflected over the x-axis.)

Study the set of table values associated with each function to see how the table values are changed by rewriting a function y=f(x) as y=-f(x).

(The y values for y2 are opposite the y values for y1 for the same x values.  The graph has been reflected over the x-axis.)

##### Use the graphing calculator to create graphs and tables of y1=ln(x) and y2=-ln(-x).
 Graphs of y1=ln(x) and y2=-ln(-x) Table values of y1=ln(x) and y2=-ln(-x)

Remember the base function y1=ln(x) begins in quadrant IV and passes through the point (1,0) and continues through quadrant I.  What happens to the graph when the y=f(x) when it is changed to y=-f(-x)?  (There are two ways to look at the reflection:  1) The graph is reflected over the origin or 2) a double reflection has taken place-first over the y axis and then over the x axis.)

Study the set of table values associated with each function to see how the table values are changed by rewriting a function y=f(x) as y=-f(-x).

(Studying the y values you can notice that y2(1)=-y1(-1), y2(2)=-y1(-2) or in general the table for y1 has been turned upside down to produce the table for y2 and the values have been changed to their opposite.  This causes the graph to be reflected over the origin or the double reflection.)

# Summary

Vertical and horizontal shift transformations

Original Function Modified Function Change

#### If y = f(x)

y = f(x)+ a  shifts the function vertically a units
y = f(x)  y = f(x-a) shifts the function horizontally a units.
Stretching and shrinking transformations
Original Function Modified Function Change
y = f(x)  y = af(x) stretches the function vertically if a>1

y = f(x)

y = af(x) shrinks the function vertically if 0<a<1
Reflections
Original Function Modified Function Change

#### y = f(x)

y = f(-x) reflect the function about the y-axis
y = f(x) y = -f(x)  reflect the function about the x-axis
y = f(x) y = -f(-x) reflect the function about the origin

4. #### Describe what transformation have been performed on the base function y1 to produce the new set of table values for y2.

5. Describe what two transformations have been performed on the base function y1 to produce the new set of table values for y2.